3 - Le Sénégal dans son appropriation de la Réforme LMD : déclinaison locale d’une Réforme « globale » - Jean-Alain Goudiaby (Journal of Higher Education in Africa, 2009)
Many transformations affect the forms and modes of operation of higher education systems. Senegal, like many African countries, has moved towards the implementation of the BMD reform in its higher education system. This reform will transform many aspects and considerations of the system. It tries, at the same time, to resolve recurrent problems by raising important issues for Senegal. How this reform, thought for Europe, is considered in the building process of the Senegalese higher education system? What challenges does it pose? What are the responses given and the limits to the implementation of this reform? These are the questions our contribution will answer. We show, in the context of the precariousness that Senegalese universities are experiencing, that the adoption of the BMD reform is at stake between binding oneself to a globalizing model and being rooted to the local context.